Full ventricular capture indicated by the qt interval function. - Gottfridsson C; Wallentin I; Dernevik L; Van Rooijen H; Van Groeningen C; Edvardsson N (Pacing & Clinical Electrophysiology, 1998)
The atrioventricular (AV) interval is critical in dual chamber (DDD) pacing in patients with hypertrophic obstructive cardiomyopathy (HOCM) to obtain full ventricular capture (FVC) with maximal reduction of the left ventricular (LV) outflow gradient and optimal LV diastolic filling. We studied the relationship of FVC, fusion, spontaneous AV conduction, and the QT interval. Methods: 11 patients with various cardiac diseases and stable AV conduction received a QT sensing Diamond,[TM] Vitatron, DDD pacemaker. Software was downloaded into the pacemaker. In the DDD pacing mode, with the QT interval measured from the ventricular pacing stimulus to the end of the T wave, the AV interval was shortened from 400 ms, in 20-ms steps, to 90 ms. At 90 ms the stimulation rate was increased by 30 heats/min and the AV interval was increased stepwise. FVC and fusion was examined on the surface ECG. Results: At 400 ms interval, spontaneous AV conduction inhibited the pacemaker. Shortening the AV interval resulted in pacing with a short QT interval. Further reduction of the AV interval resulted in a longer QT interval up to a point where the QT interval became stable. This point, the bending point in the plot of measured QT interval versus shortened AV intervals, coincided with the point of FVC. The relation of the QT-AV interval plot and the point of fusion was comparable when lengthening the AV interval at a 30 beats/min faster stimulation rate. Conclusion: The bending point in the QT interval versus AV interval plots showed a good correlation with the FVC and fusion points observed on ECG. The results suggest that automatic discrimination between fusion and full capture using QT interval measurements may be feasible.